2019
DOI: 10.5588/ijtld.19.0127
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity and transmission dynamics of M. tuberculosis in Africa: a systematic review and meta-analysis

Abstract: BACKGROUND: Mycobacterium tuberculosis complex (MTBC) and its human host are the most competent organisms with co-evolutionary trajectory. This review determined the phylogeography, clinical phenotype-related genotype and transmission dynamics of MTBC in Africa.METHODS: Spoligotyping and mycobacterial interspersed repetitive units-variable number tandem repeats (MIRU-VNTR) based articles from Africa published in the English language were included. Articles were retrieved from PubMed and Scopus on 12 May 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Our results demonstrated that majority of the 107 M. tuberculosis strains belonged to lineage 4-the most widespread lineage and among the more virulent globally [67]. The predominant clades identified in this lineage were LAM (29%), T (21.5%) and Haarlem (19.6%), which were reported in Algeria and in Northern African countries as large common clades [68]. The most prevalent sub-lineage LAM 9 (SIT 42, 13.1%) is predominant in North Africa as well as in a number European countries such as Spain, Italy and Belgium, sharing a close cluster with Northern Africa countries [69].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 57%
“…Our results demonstrated that majority of the 107 M. tuberculosis strains belonged to lineage 4-the most widespread lineage and among the more virulent globally [67]. The predominant clades identified in this lineage were LAM (29%), T (21.5%) and Haarlem (19.6%), which were reported in Algeria and in Northern African countries as large common clades [68]. The most prevalent sub-lineage LAM 9 (SIT 42, 13.1%) is predominant in North Africa as well as in a number European countries such as Spain, Italy and Belgium, sharing a close cluster with Northern Africa countries [69].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 57%
“…This is particularly true for M . tb , where the interaction of genotypic variation among different strains with human genetic polymorphism play a prominent role in the epidemiology of TB diseases [ 4 7 ] . The overall epidemiology of MTBC species is influenced by the environment, with its frequency and distribution being dependent on social, economic, and ecological causes [ 4 , 8 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The observation of a shift from predominant pulmonary TB to predominant LN-associated TB in certain geographic regions like Ethiopia, is provocative. The link between Mtb lineages and type of TB (PTB Vs EPTB) is unclear [76,77] and some association between Mycobacterium africanum (MAF) and EPTB [78][79][80] have been reported. In general, LD formation profiling among Mtb and MAF isolates disaggregated by types of TB (EPTB Vs PTB) might narrow the existing knowledge gap.…”
Section: Ld-positive Mtb In Pulmonary and Extra Pulmonary Tbmentioning
confidence: 99%